Strengthening Digital Capabilities and Entrepreneurship For SMEs in the Creative Economy Sector During a Pandemic - Leni Cahyani; Dandy Marcelino; Rahmat Hidayat (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2023)
An important aspect in the development of the local economy is MSMEs' ability to support productive human resources, allowing people to live their lives as a means of earning a living. Entrepreneurship is characterized by the ability to transform current resources into goods and selling points via the use of ingenuity. The Covid-19 pandemic sparked the growth of micro, small, and medium-sized businesses (MSMEs). The pandemic of Covid-19 has slowed most economic sectors, particularly MSMEs. Many MSME performers are unable to grow and end up in bankruptcy because of the overabundance. This is the reason why small and medium-sized businesses (SMEs) are embracing digitization initiatives. Using a marketplace (intermediary) and social media as a marketing strategy is the method of digitalization. Digital MSME players must also be able to collaborate with netizens in promoting their goods and services, as outlined in this article. Because of this, the digital MSME development strategy is a viable option to safeguard small businesses from the Covid-19 pandemic. This article uses a process known as a literature review to examine numerous works on the growth of digital small and medium-sized enterprises (SMEs). According to this article, amid the Covid-19 pandemic in Indonesia, the growth of digital MSMEs has emerged as a viable option for saving and establishing a digital enterprise.